MICROCREDIT FOR MICRO-ENTREPRENEURS DEVELOPMENT IN ENDE DISTRICT - Ellen Rusliati; Mulyaningrum Mulyaningrum; Mujibah Achyar Sufyani (Faculty of Economic and Business, University of Pasundan, 2018)
This study aims to examine the use of microcredit to improve business. Developing micro-entrepreneurs can create jobs to prevent urbanization and reduce poverties. The problems are micro-entrepreneur which are less professional to manage and low productivity. This study uses descriptive and qualitative analysis for 18 micro-entrepreneurs which got machine from Industrial Ministry. The largest contribution of Gross Regional Domestic Product of Ende District is the agricultural sector by 61.35%; its largest productions are cassava, rice, coffee, hazelnut, cashew, and cocoa. The results showed that contribution margin is still low, highly dependent on the season and manually processed; marketing are mostly done by direct sales, and shortage of capital. They need loan to increase the business, but improper utilization of capital can bring some difficulties. They must get some trainings and consultations either before get or used micro credit, because made micro-entrepreneurs have higher risk although they give higher profitability.